KEBIJAKAN PENYULUHAN HUKUM PADA KANWIL KEMENTERIAN HUKUM DAN HAM KALIMANTAN TIMUR - Umi Laili (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
Indonesia is law state that means Unity State Of Republic Indonesia is State which based on of law (rechtsstaat) and not based on of power (machtsstaat). Consequently each, every Indonesia citizen obliged to bow and law abiding which go into effect.In order to improving law in all society coat so that can be created awareness and compliance of law for the sake of the straighten of rule of law in Unity State Of Republic Indonesia, required counseling of law.In this time we earn to feel incidence of law cultural degrease in society environment with downhill indication is decrease of mount society appreciation of law including government officer. Downhill of awareness of rights and obligations of society, and also compliance of society marked at the height of transgression number, including decreased trust of society to enforcer law of government officer. This matter can be seen from to the number of mass conflict between student, conflict between society citizen element, including so many violent demonstration which is anarchist. Thereby it needed effort to improve of society sense of justice, passing by counseling of law activity.Counseling of law carried out with a purpose to realize better society sense of justice so that each, every society member realize and involve its rights and obligations as citizen and realizing culture punish in conscious behavior and attitude, obedient, and law-abiding and also respect Human right.This research use quantitative research type, where primary data come from informant of Regional Ministry Office of Law and Human right. While data of seconder are form of literature either from book, erudite copy, research report, and documents related to this topic of research Result of research indicate that there are 2 (two method) counseling of law executed by Regional Ministry office of Law and Human right of East Kalimantan that is method counseling of indirect and direct law.Efficacy of activity of counseling of law can be seen from is effective of him punish in society, law will be effective walk if the law have reached the target of desired, especially by form punish and also by executor of pertinent law. Law expressed effective if behavioral society citizen of me as expected or desired by law.Effective counseling of law can influence by some factor, According to Soerjono Soekanto that the factor there are five, that is : its own Law factor, factor Enforcer of Law, Medium factor and facility, Society factor, and also Culture factor. Where part of which is one with the other shares interact and may not interfere in among one with the other. If each the shares fulfilled and walk as according to its role, hence can be ascertained by existence of norm/law order will go into effect effectively in life of cultured society of law.